Pedagogical aspects of the formation of communication skills in French - Seisekeyeva, N.B.; Chnane-Davin, F.; Askarova, G.K.; Bokizhanova, G.K. (KU Publ., 2022)
This article discusses the problems and prospects of the development and teaching of French as a second foreign language in the Republic of Kazakhstan. The necessity of the improvement of multilingualism in Kazakhstan is a priority for the evolution of the state in modern conditions. Special attention is paid to the contribution of the French Embassy in Kazakhstan to the active development of French as a second foreign language. The article deals with the historical moments of the development of the French language, the prospects of learning French, the current state of the French language in Kazakhstan. We provide the results of a scientific and analytical survey on the use of pedagogical platforms for the formation of communication skills. This qualitative study revealed methods for the development of students’ oral communication in French. During our research, we have identified the need to develop the formation of communication skills in French through pedagogical platforms. The results of this scientific work will be available to teachers of French as a foreign language.
Француз тілінде студенттердің коммуникативтік дағдыларын қалыптастырудың педагогикалық аспектілері
Формирование у студентов коммуникативных навыков на французском языке: педагогические аспекты
Keywords: French; francophone; oral communication; pedagogical platforms; distance education; teaching methods; pedagogical aspect; national prospects